Outage probability and bit‐error rate analysis of distributed antenna systems in multicell environment. Issue 9 (1st June 2013) - Liu, Yuxi; Liu, Ju; Guo, Weidong; Xu, Hongji; Zhang, Guowei; Yang, Xiaohui
Abstract : In this study, the authors investigate the outage probability and bit‐error rate (BER) of distributed antenna system in downlink multicell environment with blanket transmission. Different from the most existing works, the variance of interference plus noise is treated as a random variable other than constant, and it is influenced by the short term fading when propagation pathloss and transmit power are given. From the perspective of information theory, the closed‐form and approximate analytical expressions of downlink outage probability and average BER in the cellular system are derived for no shadowing and shadowing scenarios, respectively. Extensive simulation results validate the theoretical analysis and demonstrate that the system performances can be significantly improved for cell‐edge users. Moreover, the proposed analytical method can obtain more accurate system performances.